2016
DOI: 10.1111/emre.12076
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Meta‐Organization: Issues for Management Studies

Abstract: International audienceIn a seminal paper, Ahrne and Brunsson coined the word ‘meta-organization’. More than a label, this word describes a challenging and stimulating concept that can be valuable for management studies when approached with different units of analysis and research methodologies. ‘Meta-organization’ refers to a central phenomenon in the contemporary world, namely the increasing importance of collective action at the level of organizations, ensuing from major issues related to sustainable develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 32 publications
2
67
0
8
Order By: Relevance
“…In doing so, it might 'unbound' itself from its more stringent assumptions, and tolerate a more diverse set of characteristics of the form. Berkowitz and Dumez (2016) also suggest the criterion of similarity may need further thought.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In doing so, it might 'unbound' itself from its more stringent assumptions, and tolerate a more diverse set of characteristics of the form. Berkowitz and Dumez (2016) also suggest the criterion of similarity may need further thought.…”
Section: Discussionmentioning
confidence: 99%
“…Their specification is that members "perform similar tasks and strive for similar things" (Ahrne and Brunsson 2008, p. 60). Berkowitz and Dumez (2016) found that the membership of oil and gas organizations in meta-organizations shows significant variety with membership commonly from different sectors and hence different types of organizations (public, private, non-governmental organizations, etc.). Similarity, may then be found more in identification with the purpose of the meta-organization than in performing similar tasks or, as Ahrne and Brunsson suggest, some other 'family resemblance'.…”
Section: Membership Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of ‘meta‐organizations’ was first coined by Ahrne and Brunsson () and further developed in a book on the topic (Ahrne and Brunsson ). It was also the subject of a recent review (Berkowitz and Dumez ). As the authors indicate, since Organizations , the seminal book by March and Simon (), organizational studies have focused mostly on ‘individual‐based organizations’, while organizations with organizations as members (i.e.…”
Section: Organization Studiesmentioning
confidence: 99%
“…Внедре-ние ОМУ всегда связано с некоторой ор-ганизационной инновацией, диффузия которой сопровождается постепенной заменой применявшихся ранее новыми реализациями более современных ме-тодов управления. При этом должно от-мечаться повышение интегральных по-казателей эффективности деятельности предприятия или нескольких предпри-ятий, если отношения между ними до-пускают тиражирование инновационных методов управления, перенесение их с одного предприятия на другое [19].…”
Section: Introductionunclassified